LEGAL CERTAINTY ON THE MISUSE OF COVID-19 SOCIAL FUNDS AS A BASIS FOR CRIMINAL AGGRAVATION - I Kadek Rinja Dwi Putra; Berliana Ayu Kusumawardani; Roynaldi Scehan (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The existence of the Covid 19 Pandemic in Indonesia some time ago can be categorized as a non-natural disaster that has been determined nationally. To anticipate and help the community, the government has disbursed social funds for the poor and affected by the policy of Enforcing Community Activity Restrictions (PPKM). There are four potential corruptions in social assistance funds in the midst of a pandemic, including: First, corruption related to the procurement of goods/services. Second, the vulnerability to recording receipts, distribution of aid and misappropriation of aid or grants from the public or private sector given to the Task Force and all ministries/institutions/local governments. Third, on the allocation of sources of funds and spending as well as the utilization of the budget in the process of refocusing and reallocating the Covid-19 budget in the APBN and APBD. Fourth, on the implementation of social assistance (social safety net) by the central and regional governments. The various cases above validate the existence of an “epidemic of corruption” amid the COVID-19 outbreak. Corruption is like a virus that spreads to fellow human beings and is dangerous. The fertility of rasuah has damaged government institutions, faded integrity, and brought about the destruction of the nation. The imperfection of the country's system, which is currently in flux after the pandemic, is the biggest weakness that opens up wider opportunities for corruption. Furthermore, people often have a logical fallacy, where they think that the more corruption cases, the better. In fact, the rampant cases of corruption being handled indicate that the function of preventing corruption has not been implemented. Therefore, the massive expansion of corruption during the pandemic is a sad portrait of the nation that should be addressed immediately. Misuse of COVID 19 funds during the pandemic through corruption by the authorities deserves to be categorized as a criminal offense, one of which is the corruption case committed by the Minister of Social Affairs as decided in Decision Number 29/PID.SUS-TPK/2021PN JKT.PST.